Analysis the Effect of Web Quality and Fulfillment on Satisfaction and Its Impact on Repurchase Intention - Rizky Fauzan; Damianus Ute (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
The purpose of this study was to analyze the effect of web quality, fulfillment, and satisfaction and its impact on repurchase intention of e-commerce customers. This type of research used survey methods, the population in this study were all Tokopedia consumers in Pontianak city-Indonesia. The sample in this study used 100 respondents using purposive sampling technique and the data analysis carried out with path analysis. Results of the first substructure was fulfillment and web quality had positive effect to satisfaction. The second substructure was the fulfillment did not effect the repurchase intention while the web quality and satisfaction variables had positive effect on repurchase intention. Satisfaction mediated the effect of fullfillment and web quality on repurchase intention.